Existence Theorem for Integral and Functional Integral Equations with Discontinuous Kernels - Ezzat R. Hassan (Abstract and Applied Analysis)
Existence of extremal solutions of nonlinear discontinuous integral equations of Volterra type is proved. This result is extended herein to functional Volterra integral equations (FVIEs) and to a system of discontinuous VIEs as well.